Mirnapis ohloweni Packer and Dumesh, new species with notes on M. inca Urban (Hymenoptera: Apidae: Eucerini) - Packer, Laurence; Dumesh, Sheila (Zootaxa, 2012)
The bee genus Mirnapis is revised. Mirnapis ohloweni Packer and Dumesh new species, is described from East of Nazca, Peru and compared to both sexes of the type species, M. inca Urban, based upon material from northern Chile. Thus, the female of the genus is described for the first time. Both sexes of both species are illustrated and variation in some important characteristics noted. The new material permits a more detailed diagnosis of the genus. Michener’s (2007) key to South American Eucerini is modified to facilitate the identification the genus and Vivallo’s (2009) key to Chilean Eucerini is emended to permit identification of M. inca.